Differences In Learning Preferences Among Medical, Dental And DPT Students - Amtul Anum; Tabassum Ahsan Qadeer (Journal of Bahria University Medical and Dental College)
Objective: To analyze the learning styles of undergraduate medical, dental and DPT (Department of physical therapy) students using the VARK questionnaire. Study Design and Setting: This cross sectional questionnaire based clinical study was conducted on 278 undergraduate students at Bahria University of Medical and Dental College in Karachi. Methodology: 150 medical, 100 dental and 28 DPT students were asked to complete VARK (Visual, Auditory, Read-write and Kinesthetic) questionnaire and their learning preferences were studied. Percentages were formulated and outcomes of each group were paralleled to conclude the result. The data was assessed using SPSS software, version 23. Statistical associations among MBBS, BDS and DPT students and gender preferences were made using chi square analysis and comparison between academic years was made with Fisher’s exact test. P<0.05 was considered significant. Results: Our result showed that 76.3% preferred unimodal style followed by bimodal (18.3%) and trimodal (5.4%). Kinesthetic (40%) was the most preferred method followed by aural (36%). There was no preferential shift with gender or academic year variation. Conclusion: According to our study, most of the undergraduate medical, dental and DPT students prefer unimodal method of learning despite of educational, gender and academic variation in the sample. None of the students preferred the quadmodal learning style. Kinesthetic was the most preferred unimodal preference.